Удмурт-ӟуч, ӟуч-удмурт кыллюкам: ог 6500 пала кыл / [редакторы-составители Т. В. Воронова, Т. А. Пояркова] - Воронова Т. В. (Удмуртия, 2019)
Экземпляры: 1 (20191127) / Инвентарный номер: 64364 / Цена: 200.00 / Сис.шифр: 81.2Удм / Авт.знак: У 30 / ББК: 81.2Удм-4